Imagery use by injured athletes: A qualitative analysis - Driediger, M.; Hall, C.; Callow, N. (Journal of Sports Sciences, 2006)
The purpose of this study was to expand our knowledge and increase our understanding of imagery use by athletes in sport-injury rehabilitation using a qualitative approach. The participants were 10 injured athletes who were receiving physiotherapy at the time they were interviewed. During the interviews, the athletes provided extensive information about their use of imagery during injury rehabilitation and it was clear that they believed imagery served cognitive, motivational and healing purposes in effectively rehabilitating an injury. Cognitive imagery was used to learn and properly perform the rehabilitation exercises. They employed motivational imagery for goal setting (e.g. imagined being fully recovered) and to enhance mental toughness, help maintain concentration and foster a positive attitude. Imagery was used to manage pain. The methods they employed for controlling pain included using imagery to practise dealing with expected pain, using imagery as a distraction, imagining the pain dispersing, and using imagery to block the pain. With respect to what they imaged (i.e. the content of their imagery), they employed both visual and kinaesthetic imagery and their images tended to be positive and accurate. It was concluded that the implementation of imagery alongside physical rehabilitation should enhance the rehabilitation experience and, therefore, facilitate the recovery rates of injured athletes. Moreover, it was recommended that those responsible for the treatment of injured athletes (e.g. medical doctors, physiotherapists) should understand the benefits of imagery in athletic injury rehabilitation, since it is these practitioners who are in the best position to encourage injured athletes to use imagery.